2020
DOI: 10.1259/dmfr.20190204
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of computer-assisted image analysis in the diagnosis of maxillofacial radiolucent lesions: A systematic review and meta-analysis

Abstract: Objectives: This study aimed to search for scientific evidence concerning the accuracy of computer-assisted analysis for diagnosing maxillofacial radiolucent lesions. Methods: A systematic review was conducted according to the statements of Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols and considering 10 databases, including the gray literature. Protocol was registered at the International Prospective Register of Systematic Reviews (CRD42018089945). The population, intervention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The reliability of computer-aided diagnosis systems has been studied recently in the diagnosis of maxillofacial radiolucent lesions and concluded that the current published evidence supports the accuracy of these methodologies in classifying the lesions compared to histopathological biopsy [ 26 ]. In this review, two interesting researches [ 14 , 27 ] discussed combined graph-based random walks segmentation with machine learning-based boosted classifiers to diagnose periapical cyst and periapical granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of computer-aided diagnosis systems has been studied recently in the diagnosis of maxillofacial radiolucent lesions and concluded that the current published evidence supports the accuracy of these methodologies in classifying the lesions compared to histopathological biopsy [ 26 ]. In this review, two interesting researches [ 14 , 27 ] discussed combined graph-based random walks segmentation with machine learning-based boosted classifiers to diagnose periapical cyst and periapical granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few meta-analyses and systematic reviews have been conducted on the utilization of AI for PL detection [58][59][60][61][62][63][64]. An important study by Silva et al [60] showed that the pooled diagnostic accuracy of CBCT for PL detection was 88.75% (95% confidence interval = 85. 19-92.30).…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck areas, only few published articles exist that address computer-aided detection and classification of lesions related to dental structures ( 8 , 17 , 30 ). A recent systematic review and meta-analysis evaluated the accuracy of the novel approaches and demonstrated the effectiveness of CAD systems in classifying lesions based on cone beam computed tomography images ( 31 ). When digital analysis of odontogenic cysts is performed using microscopy images, especially for discriminating odontogenic keratocysts and radicular cysts, a variation of 86% to 100% was observed between the least and most accurate classification methods of the eligible studies, indicating a very promising future for an automated cyst class prediction.…”
Section: Discussionmentioning
confidence: 99%